Characterization of SiC nanowires grown by APCVD using single precursors - Rho, D.-H.; Kim, J.-S.; Byun, D.-J.; Yang, J.-W.; Lee, J.-H.; Kim, N.-R. (Materials Research Society Symposium Proceedings, 2005)
SiC nanowire was grown by APCVD using single precursors. Grown SiC nanowires had 10-60nm diameters and lengths of several micrometers. Nanowire's diameters and lengths were varied with kind of catalysts. Nanowire's growth scheme was divided by two regions with diameter of nanowire. At first region, nanowire was grown by VLS (vapor-liquid-solid) mechanism, but at the second region, nanowire growth was made by VS (vapor-solid) reaction. These differences were made from limitations of growth rate and deactivation effects. Growth temperature, time and flow rates of source gases were affected nanowire's diametesr and its lengths. And kind of catalysts, coating methods and precursors were affected growth direction and microstructures too. ？ 2005 Materials Research Society.